Religiusitas, Penyesuaian Diri dan Subjektive Well Being - Muzakkiyah, Nurul; ., Suharnan (Persona:Jurnal Psikologi Indonesia, 2016)
The purpose of this study to examine the relationship between religiosity andconformity with subjective well being in jamaan Muslim Al Hidayah Surabaya. Thesubjects were 70 members of the congregation Al Hidayah Surabaya at the age of 50-60years. Data obtained from the religiosity scale, adjustment and subjective well beingtested using statistical regression. The results showed that there is a relationship betweenreligiosity, adjustments with subjective well being in jamaan Al Hidayah Surabaya withthe value F = 71.848 and P = 0.000 (p <0.01). The results of the partial correlationbetween religiosity and subjective well being shows F = 0.808 and p = 0.000 (p <0.01)and the partial correlation between adjustments with subjective well being shows F =0.815 and p = 0.000 (p <0.01).Keywords : Religiosity, Adjustment, Subjective well being